2017
DOI: 10.1128/aem.00039-17
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Search for Ionizing-Radiation-Responsive Elements in Deinococcus radiodurans Reveals a Regulatory Role for the DNA Gyrase Subunit A Gene's 5′ Untranslated Region in the Radiation and Desiccation Response

Abstract: Tight regulation of gene expression is important for the survival of , a model bacterium of extreme stress resistance. Few studies have examined the use of regulatory RNAs as a possible contributing mechanism to ionizing radiation (IR) resistance, despite their proffered efficient and dynamic gene expression regulation under IR stress. This work presents a transcriptome-based approach for the identification of stress-responsive regulatory 5' untranslated region (5'-UTR) elements in R1 that can be broadly appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Typhimurium, the primary metabolites in these cells are very distinct depending on whether they are un-irradiated or freshly irradiated or stored for 24 h post EB irradiation (Figure 1, 2). The response of bacterial cells to stressors such as acid, temperature, and ionizing radiation have been extensively studied (Foster, 1991; Arsène et al, 2000; Castanié-Cornet et al, 2010; Daly, 2012; Pin et al, 2012; Swenson et al, 2012; Castillo and Smith, 2017; Villa et al, 2017). Recently, we have shown that E. coli O26:H11 when exposed to acid stress (pH 3.6), the key differentially expressed pathways were peptidoglycan biosynthesis, purine metabolism, D-Glutamine/D-glutamate metabolism, nitrogen metabolism, unsaturated fatty acid biosynthesis, and inositol phosphate metabolism (Shayanfar et al, 2018 J. Appl.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium, the primary metabolites in these cells are very distinct depending on whether they are un-irradiated or freshly irradiated or stored for 24 h post EB irradiation (Figure 1, 2). The response of bacterial cells to stressors such as acid, temperature, and ionizing radiation have been extensively studied (Foster, 1991; Arsène et al, 2000; Castanié-Cornet et al, 2010; Daly, 2012; Pin et al, 2012; Swenson et al, 2012; Castillo and Smith, 2017; Villa et al, 2017). Recently, we have shown that E. coli O26:H11 when exposed to acid stress (pH 3.6), the key differentially expressed pathways were peptidoglycan biosynthesis, purine metabolism, D-Glutamine/D-glutamate metabolism, nitrogen metabolism, unsaturated fatty acid biosynthesis, and inositol phosphate metabolism (Shayanfar et al, 2018 J. Appl.…”
Section: Discussionmentioning
confidence: 99%
“…Strain development. The plasmid pRadGroGFP, which has been previously used to assess gene expression levels, was cut with restriction sites XhoI and BamHI (17). A gblock (IDT) was then used to replace the ApaI site with a SacII site.…”
Section: Methodsmentioning
confidence: 99%
“…Further optimization and characterization has been performed for the constitutive promoter of groES by minimization, resulting in more consistent gene expression across a range of conditions compared to the full-length promoter, as well as biological insight into 5= regulation of gene expression in D. radiodurans (15). The minimized 236-bp groES promoter is now routinely used in D. radiodurans for fundamental characterization of metabolic pathways, biological responses to radiation and desiccation, and regulatory pathways including sRNA interactions (2,10,(16)(17)(18)(19)(20). Additional investigations attempting to characterize genetic elements in D. radiodurans have led to identification of three other strong constitutive promoters (PresU, PtufA, and PtufB) and incorporation of Pspac, a strong inducible promoter originating from Bacillus subtilis (12).…”
mentioning
confidence: 99%
“…Deinococcus radiodurans is a Gram-positive bacterium that exhibits extreme resistance to high level of oxidative stresses, including ultraviolet C radiation, ionizing radiation (IR; X-and Gamma-rays), and desiccation (Krisko and Radman, 2013;Shuryak et al, 2019). Extensive studies over the last decades have shown that the extremotolerant phenotypes of D. radiodurans develop from a combination of different physiological determinants and well-regulated molecular mechanisms, such as proteome protection and small RNA (sRNA) regulations (Daly, 2009;Slade and Radman, 2011;Tsai et al, 2015;Villa et al, 2017;Chen et al, 2019;Gao et al, 2020). Deinococcus radiodurans has also evolved strong antioxidant systems to enable efficient removal of reactive oxygen species (ROS) generated from oxidative stress (Markillie et al, 1999;Slade and Radman, 2011;Jeong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%